Alcohol Content in the 'Hyper-Reality' MTV Show 'Geordie Shore'. (21st January 2018) - Lowe, Eden; Britton, John; Cranwell, Jo
Abstract : Alcohol content, including branding, is highly prevalent in the MTV reality TV show 'Geordie Shore' Series 11. Current alcohol regulation is failing to protect young viewers from exposure to such content. Abstract: Aim: To quantify the occurrence of alcohol content, including alcohol branding, in the popular primetime television UK Reality TV show 'Geordie Shore' Series 11. Methods: A 1-min interval coding content analysis of alcohol content in the entire DVD Series 11 of 'Geordie Shore' (10 episodes). Occurrence of alcohol use, implied use, other alcohol reference/paraphernalia or branding was recorded. Results: All categories of alcohol were present in all episodes. 'Any alcohol' content occurred in 78%, 'actual alcohol use' in 30%, 'inferred alcohol use' in 72%, and all 'other' alcohol references occurred in 59% of all coding intervals (ACIs), respectively. Brand appearances occurred in 23% of ACIs. The most frequently observed alcohol brand was Smirnoff which appeared in 43% of all brand appearances. Episodes categorized as suitable for viewing by adolescents below the legal drinking age of 18 years comprised of 61% of all brand appearances. Conclusions: Alcohol content, including branding, is highly prevalent in the UK Reality TV show 'Geordie Shore' Series 11. Two-thirds of all alcohol branding occurred in episodes age-rated by the British Board of Film Classification (BBFC) as suitable for viewers aged 15 years. The organizations OfCom, Advertising Standards Authority (ASA) and the Portman Group should implement more effective policies to reduce adolescent exposure to on-screen drinking. The drinks industry should consider demanding the withdrawal of their brands from the show. Short Summary: Alcohol content, including branding, is highly prevalent in the MTV reality TV show 'Geordie Shore' Series 11. Current alcohol regulation is failing to protect young viewers from exposure to such content.